Penerapan Model Rapid Aplication Development Dalam Sistem Absensi Berbasis Web Guru Pada Siswa Bina Gita Gemilang - Yantoni, Medi; Nurjaman, Rifqi Gingin; Sari, Fiona; Zuraidah, Eva (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Attendance is a student data collection process carried out by a teacher in an organization. In the world of education, absenteeism is one of the most important factors in the discipline aspect that shows the values ​​of obedience, obedience, and order. In general, the attendance process usually still uses a manual sistem, but usually it is not wrong if it is still used.However, the school must also be able to follow the current developments in order to be able to minimize the problems caused by the use of manual attendance. Because in practice there are still problems in student data collection who still use manual sistems such as the absence of a student who often leaves absent through other students and even goes home prematurely.The development of the internet is currently growing rapidly, this can certainly be utilized by creating an online attendance sistem using the RAD method. The application can be used when the teacher is unable to attend class. This attendance was created using the PHP programming language with the Code Igniter framework and MySQL database